PENGARUH INVESTASI DALAM NEGERI DAN INFLASI TERHADAP JUMLAH UANG BEREDAR DALAM ARTI LUAS DI INDONESIA PERIODE 2004-2015 - Anggun Permatasari; Rahmita budiartiningsih; Rosyetti ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study conducted in Indonesia period 2004-2015. The purpose of this study was to determine the effect of domestic investment and inflation on the money supply in a broad sense the period 2004-2015. The research uses secondary data 2004-2015 period were sourced from Bank Indonesia, Badan Pusat Statistik and Badan Kordinasi Penanaman Modal. In this study using multiple linear regression analysis using SPSS 20.0 analysis tools. Data used is the 13-year time series data. Based on the result of tests performed by t test on each variable can be concluded that the investment in the country have a significant effect on the money supply in a broad sense in Indonesia, while the variable inflation is positive but not significant effect on the money supply in a broad sense. Simultan test results showed domestic investment variables and inflation have a significant effect on the money supply in abroad sense in Indonesia period 2004-2015 with F test of 55,836 with probability of 0,000 with R2 values of 0,909 wich implies 90,9% of the money supply in a broad sense in indonesia affected by domestic investment and inflation, while the rimaining 9,1% is influenced by other variables outside the reseaceh.Keywords : Domestic Investmenent, Inflation, and Money Supply